The display and showcase design for sensitive and non-sensitive artifacts in peninsular Malaysian museums / Norashikin Abdul Karim - Abdul Karim, Norashikin (2010)
This thesis's motivation is awareness on artifact preservation and care complications in museum display showcases particularly in tropical countries. For long-term artifact care, world renowned museums utilise durable showcase designs with state-of-art security techniques. In Malaysia, the climate, lack of expertise and knowledge in showcase design can exacerbate artifact deterioration. A specific design guideline for display showcases must be imposed with 'The Antiquity Act 1976' and ICOM (International Council of Museums) guideline. The literature in museum study is extensive but few address this topic. The 4 methods of measurement used are: structured interview with experts, on-site measurement of showcases, display and environmental performance (light intensity, relative humidity and temperature) on artifact preservation, post occupancy evaluation)/on-site observations and questionnaires to measure visitors ' perception on the showcase displays. The 3 museums selected are: Islamic Art Museum Malaysia, National Museum and Terengganu State Museum. Display showcases selection entailed 3 inventory process; Inventory I (66 units), Inventory II (49 units) and Inventory III (35 units). The selection was made based on 5 factors that are: the museums' mission, selected 5 main artifacts, 2 showcase types (wall mounted and free standing), display strategies and artifact categories. Main aspects evaluated: display showcase design, accessories and materials, lighting, caption/text, artifact placement and showcase preservation. The findings show each museum has different design characteristics like dimension, security system, material, accessories and lighting that are suitable to the philosophy and objective of each museum. It was concluded that the Islamic Art Museum Malaysia adheres more closely to the ICOM standards for display showcases design and artifact care. The findings on the preservation of sensitive and non-sensitive artifacts in the display showcases at the three museums show that each museum has its own strengths and weaknesses in terms of artifact placement, the placement of text/caption, position of lighting, the temperature, relative humidity and light intensity readings plus visitors' comments and perception. It is hoped that this thesis will produce a museum display design guideline for museums in Peninsular Malaysia for 2 categories of sensitive artifacts and 3 categories of non-sensitive artifacts will become a useful reference to curators, conservators and museum display showcase designers in Malaysia.